Metamaterial-based passive radiative cooling technology - Er, Jun Liang (Nanyang Technological University, 2021)
The ever-increasing global warming emissions due to increased energy consumption due to thermal systems in buildings are set to increase. Solar irradiance is without a doubt the largest contributor to the reason why cooling demand during peak sun hours is the highest. More can be done to lower the peak cooling demand in buildings. One proposed solution would be the radiative cooling process through metamaterials. By minimizing the absorption of solar irradiance and maximizing material radiation. Cooling the surface of the metamaterial even during peak sun hours is possible. Reducing the amount of heat that gets into the buildings. Lowering cooling demand even during peak sun hours. This project is a research about how the radiative cooling process can be achieved using metamaterials by manipulating the absorptivity/emissivity characteristics of different wavelengths. Low absorptivity/emissivity in the visible light range, high absorptivity/emissivity in the mid infrared range would be needed to help achieve the radiative cooling process during daytime. Lumerical FDTD software is used for the simulations and generation of the results of the absorptivity/emissivity graphs of each metamaterial. MATLAB is used for the generation of data points from mathematical formulas. This project will help to compare the results of existing engineered radiative cooling metamaterials.